The Supramolecular Structural Chemistry of Pentafluorosulfanyl and Tetrafluorosulfanylene Compounds - Liebing, Phil (Chemistry, 2021)
The analysis of crystal structures of SF(5)‐ or SF(4)‐containing molecules revealed that these groups are often surrounded by hydrogen or other fluorine atoms. Even though fluorine prefers F⋅⋅⋅H over F⋅⋅⋅F contacts, the latter appeared to be important in many compounds. In a significant number of datasets, the closest F⋅⋅⋅F contacts are below 95 % of the van der Waals distance of two F atoms. Moreover, a number of repeating structural motifs formed by contacts between SF(5) groups was identified, including different supramolecular dimers and infinite chains. Among SF(4)‐containing molecules, the study focused on SF(4)Cl compounds, including the first solid‐state structure analyses of these reactive species. Additionally, electrostatic potential surfaces of a series of Ph‐SF(5) derivatives were calculated, pointing out the substituent influence on the ability of F⋅⋅⋅X contact formation (X=F or other electronegative atom). Interaction energies were calculated for different dimeric arrangements of Ph‐SF(5), which were extracted from experimental crystal structure determinations.